Imaging Characteristics and Histopathological Correlation in Borderline Ovarian Tumors: A Clinical Study - Sadia Asghar, Mehreen Zafar, Shazia Ashraf, Durre Shahwar, Ammara Sanam, Benish Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Borderline ovarian tumors (BOTs) are a unique group of epithelial ovarian neoplasms that exhibit cellular proliferation and nuclear atypia without stromal invasion. They pose diagnostic challenges due to overlapping imaging features with benign and malignant lesions. Accurate preoperative assessment integrating radiological and pathological evaluation is critical for appropriate surgical planning, especially in reproductive-age women where fertility preservation is a concern. Objective: To evaluate the imaging characteristics of BOTs on ultrasound and MRI and correlate these findings with histopathological outcomes in patients presenting at a tertiary care hospital in Pakistan. Methods: This cross-sectional study was conducted at the Niazi Welfare Foundation Teaching Hospital, Sargodha, from January 2023 to June 2023. Sixty female patients aged 20–60 years with adnexal masses suspicious for BOTs were included. All underwent transvaginal ultrasound and contrast-enhanced MRI prior to surgery. Imaging features such as multilocularity, septations, papillary projections, mural nodules, solid components, and ascites were recorded. Histopathology of excised specimens served as the gold standard. Statistical analysis was performed using SPSS v26.0, and chi-square tests were applied to determine correlations. Results: The mean age was 35.7 ± 9.8 years, with most cases in the 31–40-year group. Histopathology confirmed 38 serous (63.3%) and 22 mucinous BOTs (36.7%). Ultrasound detected multilocular cysts in 81.7% and papillary projections in 55% of cases, whereas MRI demonstrated superior detection rates (90% and 70%, respectively). MRI showed higher sensitivity (91%) and specificity (88%) compared with ultrasound (78% and 72%). Papillary projections and mural nodules correlated strongly with BOT histopathology (p < 0.01). Conclusion: MRI offers superior diagnostic accuracy over ultrasound in identifying BOTs, but histopathology remains the gold standard. Recognition of key imaging features can improve early diagnosis, guide surgical strategies, and support fertility-preserving management. Keywords: Borderline ovarian tumors, Ultrasound, MRI, Histopathology, Serous, Mucinous